Time dependent temperature distribution model in layered human dermal part - Acharya, Saraswati; Gurung, DB; Saxena, VP (Kathmandu University Journal of Science Engineering and Technology, 2013)
The paper developed application of finite element method with linear function in the study of temperature distribution in the layers of dermal part-stratum corneum, stratum germinativum, papillary region, reticular region and subcutaneous tissues as elements. The method is applied to obtain the numerical solution of governing differential equation for one dimensional unsteady state bio-heat transfer using suitable values of parameters that effect the heat transfer in human body. The numerical results obtained are exhibited graphically for various atmospheric temperatures for comparative study of temperature distribution profiles. The loss of heat from the outer surface of the body to the environment is taken due to convection, radiation and sweat evaporation.